Leveraging Video Essays for Students’ Vocabulary Enhancement in EFL Class - Julianz Saputra Urel Patoding; Ryan Rayhana Sofyan; Fauzan Hari Sudding Sally (State University of Makassar, 2025)
This study aims to examine the enhancement of students’ vocabulary after the application of video essays in an EFL classroom. The researcher employed a pre-experimental method using one group pre-test and post-test design. Data were collected through vocabulary tests and analyzed using the Wilcoxon Signed Rank Test and N-Gain analysis. The participants were 11th-grade students at SMA Negeri 5 Tana Toraja, with a sample of 33 students. The vocabulary test focused on five aspects: meaning, word class, spelling, word use, and pronunciation. The Wilcoxon test results showed significant enhancement across all aspects with p-values less than 0.05, indicating that the gains were statistically significant. The N-Gain values ranged from 0.27 to 0.55, classified as moderate enhancement. These findings suggest that video essays, by combining visual and auditory elements, support vocabulary enhancement by providing contextualized, multimodal input. It is concluded that video essays can significantly enhance students’ vocabulary knowledge and are a promising tool for EFL instruction.Keywords: Video essay, vocabulary enhancement, EFL learners, multimodal learning